Assessment of the genetic diversity of Atlantic bottlenose dolphin (Tursiops truncatus) strandings in the Mississippi Sound (USA) - Mark A. Arick II; Nelmarie Landrau-Giovannetti; Chuan-Yu Hsu; Corrinne E. Grover; Stephen Reichley; Zenaida V. Magbanua; Olga Pechanova; Debra Moore; Ehsan Kayal; Anna Linhoss; Theresa Madrigal; Mark Peterman; et al. (PLoS ONE, 2025)
The common bottlenose dolphin ( Tursiops truncatus ) is a key marine mammal species in the Gulf of Mexico, playing an essential role as a top predator. This study investigates the genetic diversity and population structure of bottlenose dolphins stranded in the Mississippi Sound from 2010 to 2021. Tissue samples (muscle, liver, lung, kidney, and brain) were collected from 511 stranded dolphins, and mitochondrial DNAs (mtDNA) were extracted for analysis. A total of 417 samples were successfully amplified and sequenced using high throughput sequencing, yielding 386 complete mitogenomes. Genetic diversity metrics, such as nucleotide and haplotype diversity, were calculated, and population structure was inferred for both mitochondrial control region (mtCR) and whole mitogenome sequences. Using the whole mitogenome, the study identified four genetically distinct populations within the Mississippi Sound, demonstrating regional variation in dolphin populations. Notably, two stranded individuals likely originated from populations outside the sampled area. The use of whole mitogenomes allowed for improved resolution of genetic diversity and population differentiation compared to previous studies using partial mtDNA sequences. These findings enhance our understanding of bottlenose dolphin population structure in the region and underscore the value of stranded animals for population genetic studies.